The 2007 eruptions and caldera collapse of the Piton de la Fournaise volcano (La Réunion Island) from tilt analysis at a single very broadband seismic station. Issue 8 (30th April 2014) - Fontaine, Fabrice R.; Roult, Geneviève; Michon, Laurent; Barruol, Guilhem; Muro, Andrea Di
Abstract Seismic records from La Réunion Island very broadband Geoscope station are investigated to constrain the link between the 2007 eruptive sequence and the related caldera collapse of the Piton de la Fournaise volcano. Tilt estimated from seismic records reveals that the three 2007 eruptions belong to a single inflation‐deflation cycle. Tilt trend indicates that the small‐volume summit eruption of 18 February occurred during a phase of continuous inflation that started in January 2007. Inflation decelerated 24 days before a second short‐lived, small‐volume eruption on 30 March, almost simultaneous with a sudden, large‐scale deflation of the volcano. Deflation rate, which had stabilized at relatively low level, increased anew on 1 April while no magma was erupted, followed on 2 April by a major distal eruption and on 5 April by a summit caldera collapse. Long‐term tilt variation suggests that the 2007 eruptive succession was triggered by a deep magma input.